Adsorption of methylene blue by using activated carbon from empty fruit bunch and palm press fiber - Siti Aisyah Radhiah, Mohamed (2012)
Empty Fruit Bunch (EFB) and Palm Press Fiber (PPF) are abundance of agricultural wastes.These fiber are basically incinerated and used in mulching purposes.Adsorption of methylene blue by using both of fiber is one way to increase the uses of them.Methylene blue is one of dyestuff that harmful to human and aquatic life.Effect of contact time, agitation speed and dosage of activated carbon is investigated.Activation the activated carbon using impregnated of KOH solution is used.Same ratio of fiber which is (1:1) (wt %) is prepared.The higher the contact time, the higher the amount of adsorption capacity obtained. At certain time there got the lower number of adsorption capacity because the contact time taken is not sufficient since the process of adsorption taking a long time to achieve the equilibrium. In term of agitation speed,170 rpm of speed gave the highest adsorption capacity compared to 200 rpm and 700 rpm. According to Langmuir isotherm model, it is showed that 170 rpm gave 5.025 mg/g of adsorption capacity.It is because the Van der Waals forces are weak to bind the molecules.So,the molecules that already attracted to the molecules surface are desorbed back if the agitation speed too high.For dosage impact,the adsorption capacity decreased sharply with the increasing of adsorbent dosage because of the overlapping of adsorption site that cause the overcrowding of adsorbent particles.